Pengaruh Promosi, Lokasi, Kualitas Bangunan Terhadap Minat Beli Pada Perumahan Annieland Cisoka Tangerang - Shalsabillah, Savira; Sugiyanto, Sugiyanto (CV. Lafadz Jaya, 2022)
The main purpose of this study is to determine the effect of promotion, location and building quality on buying interest in Annileand Cisoka Tangerang housing. The sampling technique used in this study was non-probability sampling. The number of respondents taken as many as 170 respondents. The analytical method used is multiple linear regression analysis. The results showed that location had a positive and significant effect on buying interest, promotions had a positive and significant effect, building quality had a positive and significant effect and location, promotion and building quality both had a positive and significant effect. Based on this research, there are research findings, namely the building quality variable has the most dominant influence on buying interest. This means that the quality of the building has the most important influence on the interest in buying Annilend housing.